Churchill on the Far East in the Second World War - Wilson, C. author. aut Link
XI, 265 p.
Keywords: Cat Wilson brings together two strands of historical scholarship: Churchill's work as a historian and the history of WWII in the Far East. Examining Churchill's portrayal of the British Empire's war against Japan, as set down in his memoirs, it ascertains whether he mythologised wartime Anglo-American relations to present a 'special relationship'.